KEPUASAN KERJA PEDAGANG PASAR KAGET DI RW 15 KELURAHAN SIMPANG TIGA KECAMATAN BUKIT RAYA KOTA PEKANBARU - Sari Oktavia Oktavia; Sumardi '; Widiastuti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to determine the level of job satisfaction the kaget market traders in Rw 15 Simpang Tiga Village District Bukit Raya Pekanbaru. The research questions guiding this study is: how high levels of job satisfaction the kaget market traders in Rw 15 Simpang Tiga Village District Bukit Raya Pekanbaru. This is a descriptive study, data were collected using a questionnaire totaling 33 point statement. Once tested, the questionnaire of 26 items declared valid, invalid and of 7 items. Otherwise the entire legal instruments with